The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s00595-016-1361-1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of frailty syndrome and risk scores on emergency cholecystectomy patients

Abstract: Frailty syndrome significantly impacts the length of hospitalization in patients undergoing emergency cholecystectomy. Although the ORs were limited, the P-Possum value was independently associated with the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…A recent retrospective analysis of the NSQIP of approximately 230,000 patients who underwent surgery from 2012 to 2015 evaluated the relationship between age, frailty, and type of surgery: this study found an increased risk of mortality and morbidity among frail patients who underwent surgery (including “minor surgery”) [41]. Frailty scores in ACC surgical setting are currently under development after which external validation will be performed [32, 42, 43].…”
Section: Resultsmentioning
confidence: 99%
“…A recent retrospective analysis of the NSQIP of approximately 230,000 patients who underwent surgery from 2012 to 2015 evaluated the relationship between age, frailty, and type of surgery: this study found an increased risk of mortality and morbidity among frail patients who underwent surgery (including “minor surgery”) [41]. Frailty scores in ACC surgical setting are currently under development after which external validation will be performed [32, 42, 43].…”
Section: Resultsmentioning
confidence: 99%
“…A retrospective study of elderly patients undergoing lung transplantation found no significant association of frailty with the duration of postoperative ventilator use or duration of stay in the intensive care unit; however, frailty was associated with a significantly greater risk of postoperative death [adjusted HR: 2.24] 24. In another study, preoperative surgical risk score of frail elderly patients undergoing emergency cholecystectomy was significantly greater than that of non-frail patients,25 which is consistent with the results of our study. Our research corroborates these findings and suggests that preoperative frailty assessment may confer an advantage in Chinese elderly patients undergoing major thoracic or abdominal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These latter components of elderly physiologic reserve have been independently verified to pose increased odds of postoperative mortality in elderly surgical cohorts and distinguish the mFI from other comorbid indexes [ 26 , 27 ]. Moreover, frailty is an important metric that is being increasingly used to predict postoperative outcomes in both our aging population [ 1 3 , 6 , 8 ] and emergency surgery [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%